Environmental justice and the new pluralism : the challenge of difference for environmentalism - Schlosberg, David (Oxford University Press, 1999)
In this theoretical treatment of the environmental justice movement, David Schlosberg demonstrates the development of a new form of critical pluralism. His study presents a challenge to both conventional pluralist thought and the practices of the major groups in the US environmental movement.